A framework of circular business models for fashion and textiles: the role of business-model, technical, and social innovation. Issue 1 (9th December 2022) - Coscieme, Luca; Manshoven, Saskia; Gillabel, Jeroen; Grossi, Francesca; Mortensen, Lars F.
Abstract: The textiles production and consumption system is a priority product-value chain for the European Commission in its 2020 Circular Economy Action Plan. The Action Plan foresees a European Union strategy for sustainable textiles in a circular economy with the aim of creating markets for sustainable and circular textile products, services, and business models. The European Environment Agency (EEA) and its Topic Center on Waste and Materials in a Green Economy (ETC/WMGE) have shown that consumption of clothing, footwear, and household textiles in Europe is on average the fourth highest category of environmental and climate impacts from a consumption perspective and from a vantage point that considers the entire life cycle. The fashion industry is responsible for more than 60% of total textiles used and clothing is expected to remain the largest application of textiles in the future. To enable a sustainable and circular textiles system, a transformation of fashion production and consumption is needed. This transformation requires innovation in business-model design, technology, and social practices through the adoption of specific policy making, education, and behavioral change enablers. In this Brief Report, we present a framework to map and advance the implementation and scaling of circular business models. This is illustrated by exploring four different circular business-model approaches for fashion and textiles, including models based on product durability; access models based on renting, leasing, and sharing; garment collection and resale; and recycling and reuse of materials. For each business-model type, we discuss enablers based on technical and social innovations and policy, behavioral change, and education.